Identification of Durum Wheat Ranges with High Grain Quality in Southern Regions - Bolkiev Zakhid Toshtemirovich; Boyborieva O'giloy Hasan's quzi; Shobirova Komila Mahmud's quzi (Scientific Trends, 2022)
Changes in the weather and climatic conditions in the republic, in the period when water shortages are beginning to be felt, require the breeding of scientifically based, experimentally tested varieties that are resistant to drought, various pests and diseases, regionalized in all regions, high-yielding and, most importantly, high-quality grains.
Keywords: southern region, durum wheat, grain quality indicators, air temperature, Karshi, Sherabad